Pricing of Consumer Innovations - Ebbing, Tobias (Logos Verlag Berlin, 2022)
Consumers are an important source of innovation. They primarily innovate out of non-monetary motivations, such as use interest, learning and social rewards. Nonetheless, increasing numbers of such consumer and user innovators recently began diffusing their creations on online marketplaces, where they price and commercialize them. This empirical work reveals that, compared to firms, consumers' different motivations to innovate affect their pricing decisions systematically in terms of cost, customer quality and competition considerations. Furthermore, it shows that customers' price evaluations differ consistently when a product is marketed as created by consumers. Two empirical, sequential mixed methods studies were conducted for testing a series of hypotheses derived from fusing pricing research with consumer and user innovation theory. The empirical work was executed in the field of indie video games. Its core quantitative analyses were carried out with data scraped from the Steam computer game marketplace. Interviews and experiments with commercializing consumer innovators and their customers scaffold the findings from the market data analyses. The generated knowledge helps (a) consumer and user innovators to shape and validate their marketing strategies, (b) business administrators to respond to an influx of consumer innovators as competitors, and (c) economists in understanding the market impacts of commercial consumer innovation diffusion.